2002
DOI: 10.1016/s0967-0645(01)00150-3
|View full text |Cite
|
Sign up to set email alerts
|

The heat transport of the Indonesian Throughflow and implications for the Indian Ocean heat budget

Abstract: The Indonesian Throughflow (ITF) is considered central to the heat budgets of the Pacific and Indian Oceans. Temperature and ocean current time series obtained within the Makassar Strait from December 1996 to early July 1998 are used to calculate heat transport of the ITF and assess its influence on Indian Ocean heat divergence. Velocity and temperature values for the surface layer that were not directly measured are extrapolated from the shallowest measurement to the sea surface using a variety of model profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 58 publications
8
103
4
Order By: Relevance
“…Difference between model results with the ITF open and closed show that there are significant changes in heat flux in regions such as seas around eastern Australia (Tasman Sea), western Australia (Leeuwin Current), southern Indian Ocean (Agulhas Current), North Pacific and South Pacific . It is likely that most of the ITF heat transport derived from the Pacific Ocean is lost to the atmosphere in the southwest Indian Ocean (Godfrey 1996), consistent with assessment from observations (Vranes et al 2002).…”
Section: The Role Of the Itf On Ocean Circulation And Climatesupporting
confidence: 76%
See 2 more Smart Citations
“…Difference between model results with the ITF open and closed show that there are significant changes in heat flux in regions such as seas around eastern Australia (Tasman Sea), western Australia (Leeuwin Current), southern Indian Ocean (Agulhas Current), North Pacific and South Pacific . It is likely that most of the ITF heat transport derived from the Pacific Ocean is lost to the atmosphere in the southwest Indian Ocean (Godfrey 1996), consistent with assessment from observations (Vranes et al 2002).…”
Section: The Role Of the Itf On Ocean Circulation And Climatesupporting
confidence: 76%
“…Numerical models and observations have indicated that changes in ocean circulation associated with the ITF are likely to affect patterns of circulation, thermal structure and air-sea exchange in widely separated regions (Macdonald 1993;Godfrey 1996;Lee et al 2002;Vranes et al 2002). In the Indian Ocean, the ITF is shown to warm the Agulhas Current and the region off the south coast of Java and Sumatra, strength the Leeuwin Current system and increase the steric height throughout the Indian Ocean (Qu et al 1994;Godfrey 1996).…”
Section: The Role Of the Itf On Ocean Circulation And Climatementioning
confidence: 99%
See 1 more Smart Citation
“…Climate). The ITF allows a substantial amount of heat to be transported from the Pacific into the Indian Ocean: on the order of 0.5 PW (Vranes et al 2002). The ITF annual transport estimates hover around 10 Sverdrups (1 Sv [ 10 6 m 3 s 21 ), with substantial seasonal and interannual variations (see Potemra 1999;Gordon 2005;Potemra and Schneider 2007;Wijffels et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…All of these species could be present in the eastern Indian Ocean, considering that these larvae grow for many months reaching large sizes, and they could be transported long distances by ocean currents. It is well documented that water from the Indonesian Seas flows into the eastern Indian Ocean (Hautala et al 2001;Vranes et al 2002), and equatorial current jets can transport water in both directions across the northern Indian Ocean (Thompson et al 2006;Sengupta et al 2007;Kantha et al 2008). This makes it likely that some species reported to be present as juveniles or adults in western Indonesia, the South China Sea, or the western Indian Ocean could also be present off western Sumatra.…”
Section: Discussionmentioning
confidence: 99%